Reformas a la Ley de Transporte Terrestre, Tránsito y Seguridad Vial con la finalidad de que exista proporcionalidad entre las penas que se imponen en dicha ley y las garantías constitucionales - Chiliquinga Centeno, Mónica Alexandra (2015)
In this paper called "AMENDMENTS TO THE LAW OF INLAND, transit and ROAD SAFETY IN ORDER TO FIND BETWEEN THE PROPORTION TO PENALTIES IMPOSED IN THIS LAW and constitutional guarantees" I developed a doctrinal study and legal analysis regarding constitutional guarantees particularly, which refers to due process, speedy process and the presumption of constitutional rights innocence of which are invested all Ecuadorians, has also given the systematic violation of the fundamental charter of Human Rights when the unconstitutional detention applies citizens who have committed a traffic violation. I developed an analysis procedure and imposition of penalties established in the Organic Law of Land Transport, Traffic and Road Safety, plus I determine the inability to address the multiple violations that occur in the normal course of transit activity, the fact they are not provided with sufficient infrastructure in what you have to do to the human elements, does not judge contraventions transit time. In the doctrinal framework I determine the background underlying the procedure to try the offenses in the country, developing an analysis of the nature and legal consequences arising from the unconstitutional application of the detention of persons who have committed a traffic violation and is punished with immediate arrest, in breach of all human, recognized and protected guarantees, including internationally. In the Legal Framework invoke the Constitution of the Republic as the standard that guarantees and gives protection to the citizens and also shapes and protection of the right of self-defense and the presumption of innocence. Emphasize the procedural form is set to the current Traffic Act and what is regulated in the Penal Code and Code of Criminal Procedure